Temperature assessment on fire resistance experiments of partially encased beams - Piloto, P.A.G. (2014)
Twelve fire resistance tests, grouped in four series, were developed using partially encased beams (PEBs) without concrete slab, for different load levels and shear condition. PEBs were built with standard hot rolled IPE100 profile and reinforced concrete between flanges. Fire resistance was determined for standard ISO834 nominal fire curve, using small fire resistance furnace and portal frame. Temperature was measured in three different sections along PEB length (S1, S2, S3), for three different materials (steel, concrete and reinforcement). Average temperature in each section and material was compared with the average temperature over length. Each series presented similar results, with good reproducibility. Special focus was given to critical temperature. The maximum temperature difference between sections and the average temperature of element length is smaller than 3.2%, 5.1%, 6.3% and 11.2%, for test series 1, 2, 3 and 4, respectively. Temperature is not uniform in cross-section. After the initial heating stage, temperature revealed a constant difference of approximately 150°C between temperatures measured inside and outside, defining two main temperature evolutions. Temperatures measured outside revealed always higher temperature level.